IMMEDIATE SYMPTOMATIC RELIEF AFTER MICROVASCULAR DECOMPRESSION FOR HEMIFACIAL SPASM: A CASE SERIES - Ali, Mumtaz; Haq, Naeem ul; Usman, Muhammad; Ishaq, Mohammad (Journal of Postgraduate Medical Institute, 2012)
Hemifacial spasmvascularcompression of the facial nerve at its Root Exit Zone (REZ) from the brainstem. Anterior inferiorcerebellor artery, posterior inferior cerebellor artery, vertebral artery commonly compress the facial nerve.Usual symptoms are progressive involuntary facial twitching.to assess the surgical outcome ofmicrovascular decompression (MVD) for Hemifacial spasm (HFS).Key Words: Hemifacial Spasm (HFS), Microvascular decompression (MVD), Facial nerve decompressionis a movement disorder characterized by intermittent, involuntary clonic or tonic clonic